Swing kinematics for male and female pro golfers - Zheng, N.; Barrentine, S. W.; Fleisig, G. S.; Andrews, J. R. (International Journal of Sports Medicine, 2008)
The purpose of the study was to compare golf swing kinematics between female and male professional golfers, with particular focus on areas where different risks of injury exist and variables that may be related to driving distance. Twenty-five LPGA golfers and twenty-five PGA golfers were tested. Customized computer software was developed to analyze kinematic data obtained with an optoelectronic system at 240 Hz. At the peak of back swing, significant differences were found in trunk forward tilt (LPGA: 25 ± 4° and PGA: 31 ± 4°), and in pelvis orientation (LPGA: 49 ± 8° and PGA: 42 ± 7°). Significantly different pelvis rotation at the ball impact was found (LPGA: - 52 ± 11° and PGA: - 42 ± 12°). The LPGA group produced significantly less angular velocities of the club shaft (2049 ± 512°/s), the left wrist (816 ± 186°/s), the right wrist (864 ± 198°/s) and the elbow extension (705 ± 109°/s) than the PGA group. The results of this study show there are differences in the swing mechanics for men and women at the professional level. Major differences were found at the wrist and elbow, where different incidences of injury were previously reported.